Diversity and infestation of ectoparasites on bats of Adams, Ilocos Norte - Obdianela, Gian Romulo R.; Reforma, Ryan Ross A.; Tagudin, Carlo Adriel J. (2013)
Ectoparasites are organism that inhabit the external area, skin or outgrowths of another organism. Infestation occurs in various duration and may be detrimental to the host. Many parasites are host specific (e.g lice) and some infest a wider range of host (e.r. ticks). In this study, bats from Adams, Ilocos Norte were observed for presence of ectoparasites. Bats were captured using mist nets and ectoparasites were collected from each bat individual. Parasites were identified and population measures (prevelence, density, and mean intensity) were calculated per species of ectoparasite. Eight species of bats and eight species of ectoparasites were observed. Out of the eight ectoparasites species, batflies were the most prevalent; specifically Nycteribiids. All infested host hardored batflies except asacotophilus kuhlii.Ticks had the highest general density, having a value of 1.0 and the highest general mean intensity,6.14. Host-specifically, fleas have the highest density, having a value of 9.0. Relativelt high values of population measures were observed on Eonycteris robusta and Scotophilus kuhlii. Generally, the species found in this area may suggest high species diversity, and also high incidence of ectoparasite infestation. Host-specificity would vary among the species of ectoparasites. Nycteribiids were found to be the most prevalent, while Ticks were the most host-specific. The parasites may favor certain hosts over others since the same parasites can be found on at least two different species of host, and sharing of the same parasites is indicative of roost sharing -- Author's abstract.